Treatment of Psoriasis With Biologic Therapy Is Associated With Improvement of Coronary Artery Plaque Lipid-Rich Necrotic Core: Results From a Prospective, Observational Study. (September 2020) - Choi, Harry; Uceda, Domingo E.; Dey, Amit K.; Abdelrahman, Khaled M.; Aksentijevich, Milena; Rodante, Justin A.; Elnabawi, Youssef A.; Reddy, Aarthi; Keel, Andrew; Erb-Alvarez, Julie; Teague, Heather; Playford, Martin P.; et al.
Abstract : Background: Lipid-rich necrotic core (LRNC), a high-risk coronary plaque feature assessed by coronary computed tomography angiography, is associated with increased risk of future cardiovascular events in patients with subclinical, nonobstructive coronary artery disease. Psoriasis is a chronic inflammatory condition that is associated with increased prevalence of high-risk coronary plaque and risk of cardiovascular events. This study characterized LRNC in psoriasis and how LRNC modulates in response to biologic therapy. Methods: Consecutive biologic naïve psoriasis patients (n=209) underwent coronary computed tomography angiography at baseline and 1-year to assess changes in LRNC using a novel histopathologically validated software (vascuCAP Elucid Bioimaging, Boston, MA) before and after biologic therapy over 1 year. Results: Study participants were middle-aged, predominantly male with similar cardiometabolic and psoriasis status between treatment groups. In all participants at baseline, LRNC was associated with Framingham risk score (β [standardized β]=0.12 [95% CI, 0.00–0.15]; P =0.045), and psoriasis severity (β=0.13 [95% CI, 0.01–0.26]; P =0.029). At 1-year, participants receiving biologic therapy had a reduction in LRNC (mm 2 ; 3.12 [1.99–4.66] versus 2.97 [1.84–4.35]; P =0.028), while those who did not receive biologic therapy over 1 year demonstrated no significant change with nominally higher LRNC (3.12 [1.82–4.60] versus 3.34 [2.04–4.74]; P =0.06). The change in LRNC was significant compared with that of the nonbiologic treated group (ΔLRNC, −0.22 mm 2 versus 0.14 mm 2, P =0.004) and remained significant after adjusting for cardiovascular risk factors and psoriasis severity (β=−0.09 [95% CI, −0.01 to −0.18]; P =0.033). Conclusions: LRNC was associated with psoriasis severity and cardiovascular risk factors in psoriasis. Additionally, there was favorable modification of LRNC in those on biologic therapy. This study provides evidence of potential reduction in LRNC with treatment of systemic inflammation. Larger, longer follow-up prospective studies should be conducted to understand how changes in LRNC may translate into a reduction in future cardiovascular events in psoriasis. Abstract : Supplemental Digital Content is available in the text.